Islamic Education in the Industrial Revolution 4.0 - Zubairi, Zubairi; Nurdin, Nurdin; Solihin, Rahmat (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The aim of this research is to find out how Islamic education is in the era of the industrial revolution 4.0. The type of research used is library research. While the data obtained is a descriptive narrative about Islamic education. The results of the study are that Islamic religious education is a process of growing and developing the intellectual, spiritual, physical, social, ethical, aesthetic, and moral potential of students. In an effort to overcome the problems of Islamic education in the modern era, the author offers ideas about the development of Islamic religious education from various perspectives. In addition, the development and implementation of Islamic religious education programs must be in line with the times, where today is the era of the industrial revolution 4.0, and schools or madrasas and universities must be able to adapt to these developments by integrating Islamic religious education with intellectual capabilities in technology.